2020
DOI: 10.1055/s-0040-1718645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 and Lockdown on Children with ADHD and Their Families—An Online Survey and a Continuity Care Model

Abstract: Background Little is known about the impact of the coronavirus disease 2019 pandemic on children with attention-deficit hyperkinetic disorder (ADHD). This study aimed to assess the impact of lockdown on children with the ADHD, and their families. Additionally, feasibility of carrying out “text message-based” intervention was evaluated. Methods An online survey was performed to evaluate the impact of lockdown on children with ADHD and their family members. Additionally, a “text message”-based intervention was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
136
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(148 citation statements)
references
References 9 publications
2
136
0
10
Order By: Relevance
“…In populations with neurodevelopmental disorders, our findings align with studies that indicated caregivers of ASD children suffered from increased stress, distress, fear, anxiety, depression, emotional dysregulation, and decreased mood during the COVID-19 period [ 9 , 21 , 50 , 51 , 52 , 53 ]. Other empirical studies investigating the impact of the COVID-19 pandemic on caregiver quality of life in families with ADHD are limited, though Shah et al reported that caregivers of ADHD children noted a higher frequency of negative interactions with their children, including increased irritability, verbal abuse, and punishment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In populations with neurodevelopmental disorders, our findings align with studies that indicated caregivers of ASD children suffered from increased stress, distress, fear, anxiety, depression, emotional dysregulation, and decreased mood during the COVID-19 period [ 9 , 21 , 50 , 51 , 52 , 53 ]. Other empirical studies investigating the impact of the COVID-19 pandemic on caregiver quality of life in families with ADHD are limited, though Shah et al reported that caregivers of ADHD children noted a higher frequency of negative interactions with their children, including increased irritability, verbal abuse, and punishment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral parent training is a well-established psychosocial treatment with the strongest evidence base showing positive outcomes in children with ADHD and improvements in parenting [ 62 , 63 , 64 , 65 , 66 ]. A preliminary study implementing telepsychology group behavioral parent training for ADHD children during the COVID-19 pandemic resulted in mostly positive outcomes with efficacy, high treatment fidelity, and parental satisfaction comparable to in-person sessions [ 67 ], and a pilot study implementing a text-message based intervention with behavioral parent training principles for ADHD proved feasible and led to satisfaction in a proportion of the caregivers [ 54 , 66 , 68 ]. While remote parent-guided programs and interventions in families with children with ADHD and/or ASD show promising results in potentially improving caregivers’ quality of life [ 57 , 63 , 67 , 69 ], these virtual strategies and interventions are still in their infancy and require further exploration [ 54 , 57 , 59 , 60 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line of our results, Zhang and colleagues' study found that children's ADHD symptoms significantly deteriorated during the COVID-19 pandemic compared to their normal state [48]. Also, inconsistent with the study of Shah, R. and colleague, who found that the lockout caused by the COVID-19 pandemic was related to deteriorating the symptoms of ADHD in half of their study participants, which was in the form of a rise in the level of activity (slight or significant), irritability, or disruptive conduct behavior [49].…”
Section: Discussionmentioning
confidence: 67%
“…57 Some families of youth with ADHD expressed appreciation for text messages helping them manage their child's symptoms. 58 Patient telehealth use during the COVID-19 pandemic posed challenges 51,59,60 (e.g., technological issues, privacy concerns, scheduling conflicts, and engaging patients physically/emotionally), with such reasons also being endorsed for missed appointments. 59 On the other hand, clinicians effectively transitioning to telehealth care reported supervisor support, and ability to adjust to technological challenges as factors contributing to their success.…”
Section: Access and Engagementmentioning
confidence: 99%